Atmospheric moisture budget and its regulation on the variability of summer precipitation over the Tibetan Plateau. Issue 2 (18th January 2017) - Wang, Ziqian; Duan, Anmin; Yang, Song; Ullah, Kalim
Abstract: Based on station observations and reanalysis data sets, the atmospheric moisture budget and its critical role in regulating the variability of summer precipitation over the Tibetan Plateau (TP) are investigated. Results indicate that the yearly variability of summer precipitation over the southern TP (STP) is mainly controlled by remote moisture transport. Local surface evaporation presents an infinitesimal interannual fluctuation, but it cannot be ignored since it is a large component of total precipitation amount in every summer. Although the incoming moisture transport at the western boundary of STP is much weaker than that at the southern boundary, it primarily influences the temporal variation of STP summer precipitation. Further analysis shows that the summer North Atlantic Oscillation (NAO) also possesses a significant impact on the variation of STP summer precipitation. A strong NAO apparently weakens the moisture transport at the western boundary, inducing less precipitation over the STP. When the NAO is strong, wave‐activity flux obviously diverges eastward from the subtropical high over northwestern Europe. Then such flux converges toward the western TP, which weakens the baroclinic vertical structure of atmospheric circulation over the TP. The NAO also influences the meridional position of the Asian jet stream and modulates the specific humidity and moisture transport at the western boundary of STP. In addition, the dynamic processes of the atmosphere are more important than the thermodynamic processes in regulating the variability of TP summer precipitation. Key Points: The interannual variability of summer precipitation over the southern TP is mainly controlled by remote moisture transport NAO influences precipitation and eastward moisture transport over the southern TP through forcing wave train and modulating Asian jet Dynamic processes of the atmosphere are more important in regulating the variability of TP precipitation